Comparative Nutrient Profiles and Functional Activities of Animal- and Plant-Based Milks and Their Roles in the Prevention of Metabolic Syndrome: A Literature Review - Khoiriyah, Romyun Alvy; Al Fakhri, Anggun Dita; Wiyatno, Farradyah Wulandari; Wahyuni, Neni Sri; Rahmawati, Laili (International Conference on Sustainable Health Promotion, 2025)
Milk contains various bioactive components that required to maintain normal human physiological activities.  Both animal and plant-based milks have benefits that can be used to minimize the risk of noncommunicable diseases (NCDs).  This review aims to compare the nutritional profiles of animal and plant-based milks and highlight their involvement in reducing the risk of NCDs.  A literature review used papers from 2014 to 202, with PubMed and ScienceDirect as key databases.  The study found that soy milk includes aglycone isoflavones, which have been demonstrated to inhibit inflammatory pathways in human intestinal cells.  On the other hand, animal milk is high in proteins, bioactive peptides, and milk fat globule membrane (MFGM) components, all of which help with brain function, immunological health, and metabolic balance. It is concluded that appropriate animal and plant-based milk consumption may help avoid degenerative diseases and promote overall health by controlling inflammation, increasing antioxidant capacity, and improving energy metabolism.  When deciding between animal and plant-based milks, evaluating their nutritional profiles and bioactive components is best to maximise possible health advantages.